Does Economic Growth Lead Employment in South Africa? - A., Temitope L. (Journal of Economics and Behavioral Studies, 2013)
This paper adopts the Toda-Yamamoto technique of causality in order to examine the direction of causality between employment and economic growth. This is to investigate whether the increase in the Gross Domestic Product (GDP) translates into increased employment or not and vice versa, in South Africa, using quarterly data from 2000Q1 to 2012Q3. South Africa has been experiencing high and increased growth for the past decade, yet the rate of employment is not significantly high. Meanwhile, the objective of the government, since the first democratic election in 1994, was to increase economic growth along with a reduction in the unemployment rate (BMR, 2011). Although the economy has been experiencing significant success of increased economic growth, it performed poorly in the area of increased employment (BMR, 2011). This study thus seeks to answer the following questions: (1) does it mean that the increase in growth does not translate to the creation of more jobs and (2) is increased economic growth not as a result of increase in employment in South Africa? The results obtained shows that causality does not run from employment to economic growth in South Africa, as the null hypothesis was not rejected at all significant levels. However, Keynes General Theory holds for South Africa, where the empirical result showed that economic growth leads employment. These results support the criticism of ‘jobless growth’ against South Africa (Kumo, 2012). The paper suggests some policy recommendations for the improvement of employment.